The Role of Institutions in Job Teleworkability Before and After the Covid-19 Pandemic - Peter Norlander; Christopher Erickson (Global Labor Organization (GLO), 2022)
The teleworkability of jobs - whether they can and will be performed remotely - has been increasingly contested in the aftermath of the COVID-19 pandemic. To explain which jobs are teleworkable and why, we emphasize the institutional context of a job, including differences among firms, union representation, professional licensing requirements, sector, and employment models. Using a novel dataset of job characteristics extracted from the text of a large sample of online job advertisements from 2010-2021, we examine various explanations for change in the availability of remote job opportunities. Prior to the pandemic, private sector, non-union, and unlicensed jobs lagged federal government, union, and licensed jobs in the growth of telework. Firms are the largest source of variance in remote job offerings relative to other obvious alternatives (technological feasibility, occupation, sector, geography). After March 2020, between-firm differences increased, and institutions influenced the rate of telework adoption.
Keywords: J60; J50; J44; J22; O30; R12; 330; flexible work; technology; institutions; institutional change; remote work